Fertility preservation for patients with malignant disease. Guideline of the DGGG, DGU and DGRM (S2k-Level, AWMF Registry No. 015/082, November 2017): recommendations and statements for girls and women = Fertilitätserhalt bei onkologischen Erkrankungen : Leitlinie der DGGG, DGU, DGRM (S2k-Level, AWMF-Registernummer 015/082, September 2017) : Empfehlungen und Statements bei Mädchen und Frauen - Dittrich, Ralf; Kliesch, Sabine; Balcerek, Magdalena; Beckmann, Matthias Wilhelm; Behringer, Karolin; Denzer, Christian; Diemer, Thorsten; Dorn, Almut; Fehm, Tanja; Germeyer, Ariane; Geue, Kristina; Ghadjar, Pirus; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Aim The aim of this official guideline published by the German Society of Gynecology and Obstetrics (DGGG) and coordinated with the German Society of Urology (DGU) and the German Society of Reproductive Medicine (DGRM) is to provide consensus-based recommendations, obtained by evaluating the relevant literature, on counseling and fertility preservation for prepubertal girls and boys as well as patients of reproductive age. Statements and recommendations for girls and women are presented below. Statements or recommendations for boys and men are not the focus of this guideline. - - Methods This S2k guideline was developed at the suggestion of the guideline commission of the DGGG, DGU and DGRM and represents the structured consensus of representative members from various professional associations (n = 40). - - Recommendations The guideline provides recommendations on counseling and fertility preservation for women and girls which take account of the patientʼs personal circumstances, the planned oncologic therapy and the individual risk profile as well as the preferred approach for selected tumor entities.